The potential impact of Trans-pacific Partnership Agreement (TPPA) on Malaysia's trade - Alavi, Rokiah; Mohd Amin, Ruzita; Mat Ghani, Gairuzazmi; Idris, Rafiq (2015)
Being a party to Trans-Pacific Partnership Agreement (TPPA) negotiation opens door of opportunities as well as challenges to Malaysia. The key concern is the involvement of the US which is feared to bring in many WTO-Plus commitments in the agreement, even though the TPPA may help to provide significant market in terms of penetrating to the US huge market. This study focuses on one issue in relation to Malaysia’s participation in TPPA. Will TPPA open doors of opportunities for Malaysia to obtain market access into member countries market in general and the US market in particular? If so what are the products that have got potentials in gaining the benefits? This study uses Gravity Model to assess the impact of TPPA on Malaysia’s trade in general and on the US in particular.